2017
DOI: 10.1111/gcb.13905
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits determine tree growth and ecosystem productivity of a tropical montane forest: Insights from a long‐term nutrient manipulation experiment

Abstract: Trait-response effects are critical to forecast community structure and biomass production in highly diverse tropical forests. Ecological theory and few observation studies indicate that trees with acquisitive functional traits would respond more strongly to higher resource availability than those with conservative traits. We assessed how long-term tree growth in experimental nutrient addition plots (N, P, and N + P) varied as a function of morphological traits, tree size, and species identity. We also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 53 publications
2
35
0
1
Order By: Relevance
“…A similar experiment in a Costa Rican wet forest found no stand-level responses to N or P, although smaller stems exhibited faster wood growth with P addition (Alvarez-Clare et al 2013). A long-term fertilization experiment in a tropical montane forest found no net effect of nutrients on aboveground productivity, reflecting both positive and negative growth responses of individual species (Baez and Homeier 2017). Finally, two recent metaanalyses have failed to detect significant responses of tropical tree growth to added nutrients (Schulte-Uebbing and de Vries 2017, Wright et al 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A similar experiment in a Costa Rican wet forest found no stand-level responses to N or P, although smaller stems exhibited faster wood growth with P addition (Alvarez-Clare et al 2013). A long-term fertilization experiment in a tropical montane forest found no net effect of nutrients on aboveground productivity, reflecting both positive and negative growth responses of individual species (Baez and Homeier 2017). Finally, two recent metaanalyses have failed to detect significant responses of tropical tree growth to added nutrients (Schulte-Uebbing and de Vries 2017, Wright et al 2018).…”
Section: Introductionmentioning
confidence: 91%
“…). A long‐term fertilization experiment in a tropical montane forest found no net effect of nutrients on aboveground productivity, reflecting both positive and negative growth responses of individual species (Baez and Homeier ). Finally, two recent meta‐analyses have failed to detect significant responses of tropical tree growth to added nutrients (Schulte‐Uebbing and de Vries , Wright et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that at small to intermediate spatial scales, neutral and environmental drivers interact to determine the structure of AMF communities (Caruso et al, 2012;Veresoglou et al, 2019). In tropical forests, there is wide array of available hosts which are likely employing a variety of strategies to cope with nutrient limitations (Nasto et al, 2014;Sayer & Banin, 2016;Baez & Homeier, 2018). Yet the degree to which individual tree species may influence the distribution and assemblage of AMF communities has yet to be firmly established in the tropics.…”
Section: ó2020mentioning
confidence: 99%
“…Changes in AMF community structure elicited by fertilization could also set feedback loops in motion (Bever et al, 2012;Neuenkamp et al, 2018). This could favor plants adapted to high nutrient availability and promote their dominance (Baez & Homeier, 2018). In the long-term, an increasing dominance of fewer plant hosts, the so called 'homogenization' of the mycorrhizal environment (Caruso et al, 2012), could support less diverse AMF communities (Alguacil et al, 2012;Liu et al, 2012;Johnson et al, 2015).…”
Section: ó2020mentioning
confidence: 99%
“…This part of the Andes was characterized as a “biodiversity hotspot” (Brehm, Pitkin, Hilt, & Fiedler, ; Homeier, Werner, Gradstein, Breckle, & Richter, ; Myers, Mittermeier, Mittermeier, da Fonseca, & Kent, ). The tested altitudinal gradient has been characterized previously in detail (Beck et al., ), and a large‐scale nutrient manipulation experiment ( NUMEX ) revealed a shift from N/P co‐limitation towards N limitation of primary productivity with elevation (Báez & Homeier, ; Homeier et al., ). Our experiment was established close to NUMEX control plots: sites used here are located at three altitudinal levels (1,000–1,140 m a.s.l., 4°11′S, 78°96′W; 2,050–2,150 m a.s.l., 3°98′S, 79°08′W; 2,880–2,960 m a.s.l., 4°12′S, 79°17′W) and are characterized by high precipitation of 3,000–4,500 mm/year with low seasonal variability (Rollenbeck & Bendix, ).…”
Section: Methodsmentioning
confidence: 99%